Catalyst for cycloaddition of carbon dioxide and preparation method thereof

By modifying ionic liquid and metal single atoms in the polyurethane structure, a catalyst for carbon dioxide cycloaddition reaction was prepared, which solved the problem of poor catalytic effect under low temperature and normal pressure conditions in the prior art, and achieved the effect of high conversion, selectivity and catalyst reuse.

CN119500265APending Publication Date: 2025-02-25SHANDONG GUOYI ZHONGYONG ENVIRONMENTAL TECH SERVICE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661410.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to use a simple process under low temperature and normal pressure conditions to achieve high conversion and selective carbon dioxide cycloaddition reactions, and the catalyst reuse rate is low.

Method used

Through light source exposure and one-step glue connection method, ionic liquid and metal single atoms are anchored in the polyurethane structure to prepare an ionic liquid-modified polyurethane metal single atom catalyst to achieve CO2 cycloaddition reaction.

Benefits of technology

Under low temperature and normal pressure conditions, the catalyst achieves high conversion and selectivity without the need for additional co-catalysts, and the catalyst is easy to recover and reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500265A_ABST
    Figure CN119500265A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a catalyst for cycloaddition of carbon dioxide, which comprises the following steps: fully dissolving a proper amount of metal precursor, triethanolamine, hydroxyethyl methylacrylate and 1-vinyl imidazole in an organic reagent to obtain a solution A; a proper amount of p-phenylene diisocyanate is fully dissolved in an organic reagent, and a solution B is obtained; fully mixing the solution A and the solution B under the protection of inert gas; the formed gel is exposed under a light source with a certain intensity, the gel is regularly rotated and lasts for a certain time in the exposure process, then the gel is subjected to constant-temperature aging treatment, and the mechanical strength of the gel is further improved; placing the gel in a flask, adding an organic solvent, and dropwise adding a certain amount of halogen alkane to obtain the ionic liquid modified polyurethane-based metal monatomic catalyst. The ionic liquid modified polyurethane-based metal monatomic catalyst provided by the invention has the advantages of simple synthesis method, mild process conditions, easy adjustment of the structural shape of the catalyst, stable structural strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic synthesis, and particularly relates to a catalyst for carbon dioxide cycloaddition and a preparation method thereof. Background Art

[0002] CO2 is the main greenhouse gas causing global warming. In recent years, researchers have been committed to developing new technologies for more efficient CO2 capture and utilization. Among them, CO2 chemical conversion is an important part of the emission reduction process and is the most widely used. Among them, CO2 cycloaddition reaction has 100% atom economy. Through chemical methods, CO2 is converted into high value-added products, such as polycarbonate, cyclic carbonate, etc. These products are widely used in packaging materials, solvents, coatings and other fields.

[0003] Due to their unique physical and chemical properties, ionic liquids have shown significant advantages in carbon dioxide capture, conversion and utilization. Compared with traditional solvents, ionic liquids dissolve more carbon dioxide at lower pressures. By designing their cations and anions, their selective absorption capacity for CO2 can be adjusted. This property can achieve selective adsorption of CO2 in mixed atmospheres, greatly improving the separation efficiency of CO2. In addition, ionic liquids have extremely low volatility and have less impact on the environment than most organic solvents. Therefore, ionic liquids are ideal catalyst components that promote the reaction of carbon dioxide with other compounds (such as alkylene oxides) to form high-value chemicals, which provides an efficient way for the chemical conversion of carbon dioxide. Summary of the invention

[0004] The key technical problem to be solved by the present invention is to provide a heterogeneous catalyst with simple synthesis method, low process cost, high structural strength and easy recycling. The catalyst can achieve high conversion rate and selectivity under low temperature and normal pressure, without the need for an external co-catalyst and without a solvent, and the reaction system is simple and the catalyst has a high reusability.

[0005] The present invention provides a method for preparing a catalyst for carbon dioxide cycloaddition, wherein an ionic liquid and a metal single atom are anchored in a polyurethane structure by simple light source exposure and a one-step bonding method, so as to prepare an ionic liquid-modified polyurethane-based metal single atom catalyst having excellent CO2 cycloaddition performance, and the method comprises the following steps:

[0006] (1) dissolving appropriate amounts of a metal precursor, triethanolamine, hydroxyethyl methacrylate and 1-vinylimidazole in an organic reagent to obtain a solution A;

[0007] (2) dissolving an appropriate amount of p-phenylene diisocyanate in an organic reagent to obtain a solution B;

[0008] (3) Under the protection of inert gas, solution A and solution B are fully mixed and stirred at a constant temperature until gelation occurs. Stirring is stopped and the mixture is quickly transferred to a mold for shaping;

[0009] (4) exposing the formed gel to a light source of a certain intensity, rotating the gel periodically for a certain period of time during the exposure process, and then subjecting the gel to a constant temperature aging treatment to further improve its mechanical strength;

[0010] (5) After the gel aging is completed, remove the excess organic reagent on the catalyst surface;

[0011] (6) placing the gel in a flask, adding an organic solvent, dropping a certain amount of halogenated alkane, and rapidly stirring to obtain an ionic liquid-modified polyurethane-based metal single atom catalyst IL-M-PU;

[0012] (7) The dried IL-M-PU is placed in a reactor, an appropriate amount of epoxide substrate is added, and a gas containing CO2 is continuously introduced to replace the air in the reaction system, and then CO2 and epoxide are cycloaddition-treated under mild reaction conditions to prepare cyclic carbonate. After the reaction is completed, the reaction system is cooled to room temperature, and the IL-M-PU is directly taken out and washed three times with deionized water and anhydrous ethanol to achieve recovery and reuse. The liquid product is qualitatively and quantitatively analyzed by gas chromatography and nuclear magnetic resonance, and the conversion rate of epoxide and the selectivity of the target product cyclic carbonate are further calculated.

[0013] Among them, the reaction equation for preparing cyclic carbonate by cycloaddition of CO2 and epoxide under normal pressure is as follows:

[0014]

[0015] The synthesis process and structural schematic diagram of the polyurethane-based metal single atom catalyst modified by ionic liquid are as follows:

[0016]

[0017] Preferably, in step (1), the types of metal precursors include but are not limited to metal oxides, metal chlorides, carbonates, sulfates, and acetates; the types of metals include but are not limited to Au, Ag, Cu, Ni, Pd, Pt, Co, Zn, Ti, Fe, Ru, Mo, Al, and Mg; the concentration of the metal precursor is 0.001 to 1 mol / L; the concentration of triethanolamine is 0.01 to 10 mol / L; the concentration of hydroxyethyl methacrylate is 0.01 to 10 mol / L; and the concentration of 1-vinylimidazole is 0.001 to 2 mol / L.

[0018] Preferably, in step (2), the concentration of p-phenylene diisocyanate is 0.01 to 10 mol / L.

[0019] Preferably, in steps (1), (2) and (6), the organic reagent includes but is not limited to a mixture of one or more organic reagents, and the types of organic reagents include but are not limited to acetonitrile, tetrahydrofuran, methanol, ethanol, 1,4-dioxane, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and acetone.

[0020] Preferably, in step (3), the inert gas includes but is not limited to argon, nitrogen, and helium; the temperature of the constant temperature stirring is 10 to 90° C., the stirring rate is 50 to 1000 rpm, and the stirring time is 5 to 1200 s.

[0021] Preferably, in step (4), the light source intensity to which the formed gel is exposed is 100 to 1000 W; the rotation rate during the gel exposure process is 1 to 20 rpm, the exposure time is 1 to 5 h, the constant temperature aging temperature is 10 to 90° C., and the aging time is 1 to 100 h.

[0022] Preferably, in step (5), the method for removing the organic solvent on the catalyst surface includes but is not limited to volatilization at room temperature and normal pressure, vacuum drying, forced air drying, and freeze drying; the shape of the catalyst includes but is not limited to block, sheet, strip, and film; the size of the catalyst is 1 to 100,000 cm 2 .

[0023] Preferably, in step (6), the halogen anion precursor of the ionic liquid is ethyl bromide, ethyl iodide, methyl bromide, methyl chloride, methyl iodide, propyl bromide, or propyl iodide; the concentration of the halogen alkane is 0.001 to 2 mol / L; the ratio of the molar amount of the metal ion to the molar amount of the ionic liquid is less than 1:10; and the stirring rate is 1 to 1000 rpm.

[0024] Preferably, in step (7), the types of epoxides include but are not limited to ethylene oxide, propylene oxide, epichlorohydrin, epibromohydrin, styrene oxide, and 1,2-butylene oxide; the CO2-containing gas introduced includes but is not limited to high-purity (100%) CO2, low-purity (0.01-10%) CO2, air, and industrial flue gas; the mild reaction conditions are low temperature and normal pressure, a temperature of 20-100°C, and a reaction time of 2-40h.

[0025] The present invention also provides a catalyst for carbon dioxide cycloaddition prepared by the preparation method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The ionic liquid-modified polyurethane-based metal single-atom catalyst provided by the present invention has the advantages of simple synthesis method, mild process conditions, easy adjustment of catalyst structure shape, and stable structural strength.

[0028] (2) The ionic liquid-modified polyurethane-based metal single atom catalyst described in the present invention successfully realizes the grafting of ionic liquids, giving the catalyst better CO2 capture ability and allowing CO2 to be better enriched on the pore surface of the catalyst, which provides an important basis for the conversion of CO2. The high activity of the metal single atom greatly promotes the ring-opening process of the epoxide. The coupling effect of the two significantly improves the catalytic effect of the catalyst in the carbon dioxide cycloaddition reaction, and high substrate conversion rate and product selectivity can be achieved without the need for an external co-catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a physical picture of the polyurethane-based catalyst synthesized in Examples 1-3;

[0030] Figure 2 This is a graph showing the CO2 cycloaddition reaction cycle test results of the IL-Co-PU catalyst prepared in Example 2. DETAILED DESCRIPTION

[0031] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Embodiment 1:

[0033] (1) 0.03 mmol of zinc acetate, 1.5 mmol of triethanolamine, 0.5 mmol of hydroxyethyl methacrylate and 0.5 mmol of 1-vinylimidazole were dissolved in 20 ml of N,N-dimethylacetamide by ultrasonication to prepare solution A;

[0034] (2) dissolving 3 mmol of p-phenylene diisocyanate in 20 ml of N,N-dimethylacetamide by ultrasonication to prepare solution B;

[0035] (3) Under the protection of N2, solution A and solution B were fully mixed and stirred at 150 rpm at room temperature until gelation occurred. Stirring was stopped and the centrifuge tube was quickly transferred;

[0036] (4) irradiating the formed gel under a 400 W light source for 2 h, rotating at a speed of 15 rpm during the irradiation process, and then placing the irradiated gel block in a 60 ° C oven for constant temperature aging for 12 h;

[0037] (5) transferring the aged gel to a vacuum oven at 60° C. for drying to remove the residual organic solvent, thereby obtaining a catalyst precursor;

[0038] (6) The dried block precursor was immersed in 20 ml of ethanol, and 0.5 mmol of ethyl bromide was added dropwise. The dropping process was rapidly stirred at 500 rpm. The obtained sample was taken out and dried in a vacuum oven at 50 °C to obtain an ionic liquid-modified polyurethane-based metal single atom catalyst (IL-Zn-PU);

[0039] (7) The dried IL-Zn-PU was placed in a reactor, 10 ml of propylene oxide was added, and a gas containing CO2 was continuously introduced to remove the air in the displacement system. The reaction was carried out at 50°C and 1 atm for 12 hours. After the reaction was completed, the reactor was cooled to room temperature, the IL-Zn-PU was taken out, and it was washed and dried with deionized water and ethanol. The liquid product was qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry and nuclear magnetic resonance. The results showed that the conversion rate of propylene oxide was 98.5% and the product selectivity was 99.5%. After 5 cycles of testing, the catalytic performance of IL-Zn-PU could still maintain a substrate conversion rate of 92.5% and a product selectivity of 97.5%.

[0040] Embodiment 2:

[0041] (1) 0.03 mmol of cobalt acetate, 1.5 mmol of triethanolamine, 0.5 mmol of hydroxyethyl methacrylate and 0.5 mmol of 1-vinylimidazole were dissolved in 20 ml of N,N-dimethylacetamide by ultrasonication to prepare solution A;

[0042] (2) dissolving 3 mmol of p-phenylene diisocyanate in 20 ml of N,N-dimethylacetamide by ultrasonication to prepare solution B;

[0043] (3) Under the protection of N2, solution A and solution B were fully mixed and stirred at 150 rpm at room temperature until gelation occurred. Stirring was stopped and the centrifuge tube was quickly transferred;

[0044] (4) irradiating the formed gel under a 400 W light source for 2 h, rotating at a speed of 15 rpm during the irradiation process, and then placing the irradiated gel block in a 60 ° C oven for constant temperature aging for 12 h;

[0045] (5) transferring the aged gel to a vacuum oven at 60° C. for drying to remove the residual organic solvent, thereby obtaining a catalyst precursor;

[0046] (6) The dried block precursor was immersed in 20 ml of ethanol, and 0.5 mmol of ethyl bromide was added dropwise. The dropping process was rapidly stirred at 500 rpm. The obtained sample was taken out and dried in a vacuum oven at 50 °C to obtain an ionic liquid-modified polyurethane-based metal single atom catalyst (IL-Co-PU);

[0047] (7) The dried IL-Co-PU was placed in a reactor, 10 ml of propylene oxide was added, and a gas containing CO2 was continuously introduced to remove the air in the displacement system. The reaction was carried out at 50 ° C and 1 atm for 12 hours. After the reaction was completed, the reactor was cooled to room temperature, the IL-Co-PU was taken out, and it was washed and dried with deionized water and ethanol. The liquid product was qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry and nuclear magnetic resonance. The results showed that the conversion rate of propylene oxide was 99.2% and the product selectivity was 99.4%. After 5 cycles of testing, the catalytic performance of IL-Co-PU can still maintain a substrate conversion rate of 93.5% and a product selectivity of 98.5%.

[0048] Embodiment 3:

[0049] (1) 0.03 mmol of aluminum chloride, 1.5 mmol of triethanolamine, 0.5 mmol of hydroxyethyl methacrylate and 0.5 mmol of 1-vinylimidazole were dissolved in 20 ml of N,N-dimethylacetamide by ultrasonication to prepare solution A;

[0050] (2) dissolving 3 mmol of p-phenylene diisocyanate in 20 ml of N,N-dimethylacetamide by ultrasonication to prepare solution B;

[0051] (3) Under the protection of N2, solution A and solution B were fully mixed and stirred at 150 rpm at room temperature until gelation occurred. Stirring was stopped and the centrifuge tube was quickly transferred;

[0052] (4) irradiating the formed gel under a 400 W light source for 2 h, rotating at a speed of 15 rpm during the irradiation process, and then placing the irradiated gel block in a 60 ° C oven for constant temperature aging for 12 h;

[0053] (5) transferring the aged gel to a vacuum oven at 60° C. for drying to remove the residual organic solvent, thereby obtaining a catalyst precursor;

[0054] (6) The dried block precursor was immersed in 20 ml of ethanol, and 0.5 mmol of ethyl bromide was added dropwise. The dropping process was rapidly stirred at 500 rpm. The obtained sample was taken out and dried in a vacuum oven at 50 °C to obtain an ionic liquid-modified polyurethane-based metal single atom catalyst (IL-Al-PU);

[0055] (7) The dried IL-Al-PU was placed in a reactor, 10 ml of propylene oxide was added, and a gas containing CO2 was continuously introduced to remove the air in the displacement system. The reaction was carried out at 50°C and 1 atm for 12 hours. After the reaction was completed, the reactor was cooled to room temperature, the IL-Al-PU was taken out, and it was washed and dried with deionized water and ethanol. The liquid product was qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry and nuclear magnetic resonance. The results showed that the conversion rate of propylene oxide was 91.2% and the product selectivity was 93.4%. After 5 cycles of testing, the catalytic performance of IL-Al-PU could still maintain a substrate conversion rate of 89.5% and a product selectivity of 90.5%.

[0056] Embodiment 4:

[0057] The preparation process and experimental operation steps of IL-Zn-PU were the same as those in Example 1, except that the reaction temperature was increased to 60°C and the reaction time was extended to 20 hours. The results showed that the conversion rate of propylene oxide was 99.3% and the product selectivity reached 99.7%.

[0058] Embodiment 5:

[0059] The preparation process and experimental operation steps of IL-Zn-PU were the same as those in Example 1, except that the reaction substrate was replaced with epichlorohydrin and the reaction temperature was increased to 60° C. The results showed that the conversion rate of epichlorohydrin was 95.2% and the product selectivity reached 96.6%.

[0060] Embodiment 6:

[0061] The preparation process and experimental operation steps of IL-Zn-PU were the same as those in Example 1, except that the reaction substrate was replaced with 1,2-butylene oxide and the reaction temperature was increased to 60° C. The results showed that the conversion rate of epichlorohydrin was 90.4% and the product selectivity reached 92.3%.

[0062] Embodiment 7:

[0063] The preparation process and experimental operation steps of IL-Co-PU were the same as those in Example 2, except that the reaction temperature was increased to 60°C and the reaction time was extended to 20 hours. The results showed that the conversion rate of propylene oxide was 99.5% and the product selectivity reached 99.7%.

[0064] Embodiment 8:

[0065] The preparation process and experimental operation steps of IL-Co-PU were the same as those in Example 2, except that the reaction substrate was replaced with epichlorohydrin, the reaction temperature was increased to 60°C, and the reaction time was extended to 20h. The results showed that the conversion rate of propylene oxide was 99.3% and the product selectivity reached 99.5%.

[0066] Embodiment 9:

[0067] The preparation process and experimental operation steps of IL-Co-PU were the same as those in Example 2, except that the reaction substrate was replaced with 1,2-butylene oxide, the reaction temperature was increased to 70°C, and the reaction time was extended to 20 hours. The results showed that the conversion rate of propylene oxide was 99.1% and the product selectivity reached 99.4%.

[0068] Embodiment 10:

[0069] The preparation process and experimental operation steps of IL-Al-PU were the same as those in Example 3, except that the reaction temperature was increased to 70°C and the reaction time was extended to 20 hours. The results showed that the conversion rate of propylene oxide was 94.7% and the product selectivity reached 95.9%.

[0070] The specific evaluation results of the catalysts of Examples 1-10 are shown in Table 1 below.

[0071] Table 1 Specific evaluation results of catalysts of Examples 1-10

[0072]

[0073] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a catalyst for carbon dioxide cycloaddition, characterized in that: The ionic liquid and the metal single atom are anchored in the polyurethane structure by simple light source exposure and a one-step bonding method to prepare an ionic liquid-modified polyurethane-based metal single atom catalyst with excellent CO2 cycloaddition performance. The method comprises the following steps: (1) dissolving appropriate amounts of a metal precursor, triethanolamine, hydroxyethyl methacrylate and 1-vinylimidazole in an organic reagent to obtain a solution A; (2) dissolving an appropriate amount of p-phenylene diisocyanate in an organic reagent to obtain a solution B; (3) Under the protection of inert gas, solution A and solution B are fully mixed and stirred at a constant temperature until gelation occurs, stirring is stopped and the mixture is quickly transferred to a mold for shaping; (4) exposing the formed gel to a light source of a certain intensity, rotating the gel periodically for a certain period of time during the exposure process, and then subjecting the gel to a constant temperature aging treatment to further improve its mechanical strength; (5) After the gel aging is completed, remove the excess organic reagent on the catalyst surface; (6) placing the gel in a flask, adding an organic solvent, dropping a certain amount of halogenated alkane, and rapidly stirring to obtain an ionic liquid-modified polyurethane-based metal single atom catalyst IL-M-PU; (7) The dried IL-M-PU is placed in a reactor, an appropriate amount of epoxide substrate is added, and a gas containing CO2 is continuously introduced to replace the air in the reaction system, and then CO2 and epoxide are cycloaddition-treated under mild reaction conditions to prepare cyclic carbonate. After the reaction is completed, the reaction system is cooled to room temperature, and the IL-M-PU is directly taken out and washed three times with deionized water and anhydrous ethanol to achieve recovery and reuse. The liquid product is qualitatively and quantitatively analyzed by gas chromatography and nuclear magnetic resonance, and the conversion rate of epoxide and the selectivity of the target product cyclic carbonate are further calculated.

2. The method for preparing a carbon dioxide cycloaddition catalyst according to claim 1, characterized in that: In step (1), the types of metal precursors include but are not limited to metal oxides, metal chlorides, carbonates, sulfates, and acetates; the types of metals include but are not limited to Au, Ag, Cu, Ni, Pd, Pt, Co, Zn, Ti, Fe, Ru, Mo, Al, and Mg; the concentration of the metal precursor is 0.001 to 1 mol / L; the concentration of triethanolamine is 0.01 to 10 mol / L; the concentration of hydroxyethyl methacrylate is 0.01 to 10 mol / L; and the concentration of 1-vinylimidazole is 0.001 to 2 mol / L.

3. The method for preparing a carbon dioxide cycloaddition catalyst according to claim 1, characterized in that: In step (2), the concentration of p-phenylene diisocyanate is 0.01 to 10 mol / L.

4. The method for preparing a carbon dioxide cycloaddition catalyst according to claim 1, characterized in that: In steps (1), (2) and (6), the organic reagent includes but is not limited to a mixture of one or more organic reagents, and the types of organic reagents include but are not limited to acetonitrile, tetrahydrofuran, methanol, ethanol, 1,4-dioxane, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and acetone.

5. The method for preparing a carbon dioxide cycloaddition catalyst according to claim 1, characterized in that: In step (3), the inert gas includes but is not limited to argon, nitrogen, and helium; the temperature of the constant temperature stirring is 10 to 90° C., the stirring rate is 50 to 1000 rpm, and the stirring time is 5 to 1200 s.

6. The method for preparing a carbon dioxide cycloaddition catalyst according to claim 1, characterized in that: In step (4), the light source intensity to which the formed gel is exposed is 100 to 1000 W; the rotation rate during the gel exposure process is 1 to 20 rpm, the exposure time is 1 to 5 hours, the constant temperature aging temperature is 10 to 90° C., and the aging time is 1 to 100 hours.

7. The method for preparing a carbon dioxide cycloaddition catalyst according to claim 1, characterized in that: In step (5), the method of removing the organic solvent on the catalyst surface includes but is not limited to volatilization at room temperature and normal pressure, vacuum drying, forced air drying, and freeze drying; the shape of the catalyst includes but is not limited to block, sheet, strip, and film; the size of the catalyst is 1 to 100,000 cm 2 .

8. The method for preparing a carbon dioxide cycloaddition catalyst according to claim 1, characterized in that: In step (6), the halogen anion precursor of the ionic liquid is ethyl bromide, ethyl iodide, methyl bromide, methyl chloride, methyl iodide, propyl bromide, or propyl iodide; the concentration of the halogen alkane is 0.001 to 2 mol / L; the ratio of the molar amount of the metal ion to the molar amount of the ionic liquid is less than 1:10; and the stirring rate is 1 to 1000 rpm.

9. The method for preparing a carbon dioxide cycloaddition catalyst according to claim 1, characterized in that: In step (7), the types of epoxides include but are not limited to ethylene oxide, propylene oxide, epichlorohydrin, epibromohydrin, styrene oxide, and 1,2-butylene oxide; the CO2-containing gas introduced includes but is not limited to high-purity (100%) CO2, low-purity (0.01-10%) CO2, air, and industrial flue gas; the mild reaction conditions are low temperature and normal pressure, a temperature of 20-100°C, and a reaction time of 2-40h.

10. A catalyst for carbon dioxide cycloaddition, characterized in that The catalyst is prepared by the preparation method according to any one of claims 1 to 9.